Evaluation of a novel immuno-magnetic assay technology for rapid detection of dengue NS1 antigen - Roy, Partha; Gaur, Ravi; Anand, Ankita (International Journal of Research in Medical Sciences, 2019)
Background: Serological diagnosis of dengue fever is based on the detection of NS1 antigen and further confirmed by the assay of dengue IgM and IgG. Rapid Diagnostic Tests (RDTs) are no longer recommended for use by the Government of India. However, there is a requirement of rapid results without compromising on the test quality. Accordingly, we undertook an evaluation of a novel cartridge-based system employing a unique table-top diagnostic device for dengue NS1 antigen by BluSense Diagnostics incorporating a patented Immuno-Magnetic Assay (IMA). Methods: A total of 309 samples were tested on unlinked anonymous basis. Each sample was tested using NS1 Ag ELISA (Microlisa, J. Mitra), ViroTrack and NS1 RDT (SD Alere) and results were recorded. Discordant samples were further tested by dengue NS1 AG ELISA (Panbio) and dengue IgG/IgM Maclisa (J. Mitra). Results: When compared with approved ELISA kits used globally the Virotrack test returned a sensitivity of 94.74%; specificity of 97.44%; PPV of 97.30%; NPV of 95% and accuracy of 96.10%. Hourly throughput is 5-6 samples. Conclusions: The Virotrack system is highly suitable as a POCT module in HCFs with low to moderate workload that employs novel technology, is rapid, user friendly and comparable to the ELISA in sensitivity and specificity. The equipment is user friendly and can work both on plasma/serum and whole blood. Model with multiple modules (3-4) will improve the throughput and turnaround time. Evaluation of this novel technology has been done in India for the first time.